Communication Strategies in Pasambahan Maurak Selo of Mando’a Manujuah Hari Tradition - Rofi’ul Walid; Riki Rikarno (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study examines communication strategies employed in the Pasambahan maurak selo procession within the Mando’a manujuah hari tradition at Nagari Tanjuang Barulak, Batipuh District, Tanah Datar Regency. Pasambahan maurak selo is a form of Minangkabau traditional communication delivered in a grief context, particularly during collective prayers on the seventh day following a death, carrying symbolic, social, and spiritual values. The study employs a qualitative descriptive approach with a communication ethnography method. Data were collected through participant observation, in-depth interviews with traditional leaders (ninik mamak), the village head, the Kerapatan Adat Nagari chief, and youth representatives, along with documentation. Data validity was ensured through triangulation, member checking, audit trail, and prolonged engagement. The findings reveal five interconnected communication strategies in Pasambahan maurak selo: symbolic, affective, representative, contextual, and participatory. Analysis using Hymes’ S.P.E.A.K.I.N.G. model confirms the procession constitutes a fully structured speech event. The study concludes that Pasambahan maurak selo is not merely ceremonial, but a mature and complex cultural communication strategy that maintains social harmony, manages collective grief, and preserves the traditional and Islamic values of the Minangkabau community.